2016
DOI: 10.4172/2572-9462.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Acute Stroke Patient with Flat Detector CT Prior to Mechanical Thrombectomy

Abstract: Flat panel detectors have revolutionized tomographic imaging in the angio suite. Recent developments in hardware and software have improved soft tissue resolution and acquisition time even further, enabling soft-tissue and perfusion imaging within the angio suite. The so called "one-stop-shop" stroke imaging with flat panel detector computed tomography (FDCT) will significantly improve door to groin times and probably have an impact on patient outcome. In the presented case a patient underwent multidetector CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding the prospects of C-arm CTP using an angiography system, the "one-stop-shop" concept has been proposed. 10,13,19) Under this concept, when a patient suspected of having stroke visits a hospital, the patient is perfusion, Beuing et al and Niu et al reported that the homology with MD-CTP was favorable and it was useful to diagnose acute cerebral infarction and decide on triage. 10,14) Royalty et al also stated that a strong correlation was noted in qualitative evaluation between C-arm CTP and MD-CTP.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prospects of C-arm CTP using an angiography system, the "one-stop-shop" concept has been proposed. 10,13,19) Under this concept, when a patient suspected of having stroke visits a hospital, the patient is perfusion, Beuing et al and Niu et al reported that the homology with MD-CTP was favorable and it was useful to diagnose acute cerebral infarction and decide on triage. 10,14) Royalty et al also stated that a strong correlation was noted in qualitative evaluation between C-arm CTP and MD-CTP.…”
Section: Discussionmentioning
confidence: 99%